Frontiers in Clinical Drug Research - Anti-Cancer Agents 2013
DOI: 10.2174/9781608057986113010003
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Cancer Therapy: The Tumor Microenvironment as Target

Abstract: Solid tumors grow within a complex microenvironment composed of diverse cell types such as fibroblasts, endothelial cells, mast cells, macrophages and immune cells that are attracted by tumor cell derived factors and embedded in an extracellular matrix. Molecular and cellular interactions between epithelial cells and cells surrounding the tumor stroma promote growth, invasion and spread of tumors. To delay or impede tumor growth, the tumor microenvironment (TME) is increasingly being explored as a potential th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 402 publications
(448 reference statements)
0
3
0
Order By: Relevance
“…This is expected due to the high percentage of monoclonal cells present within BM from which the constructs were originally derived and the relatively simple type I collagen hydrogels in which they were seeded. These high myeloma constructs indicated the importance of the in vivo tumor microniche for the in vitro study of long-lived plasma cells because without these essential components or additional factors introduced, plasma cells are unable to survive for 5 days in vitro (Cassese et al, 2003; Arce et al, 2004; Cretu & Brooks, 2007; Schwendener & Mete, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is expected due to the high percentage of monoclonal cells present within BM from which the constructs were originally derived and the relatively simple type I collagen hydrogels in which they were seeded. These high myeloma constructs indicated the importance of the in vivo tumor microniche for the in vitro study of long-lived plasma cells because without these essential components or additional factors introduced, plasma cells are unable to survive for 5 days in vitro (Cassese et al, 2003; Arce et al, 2004; Cretu & Brooks, 2007; Schwendener & Mete, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that in order to maintain their phenotype in culture, PCs require components of the tumor microenvironment such as survival factors and/or BM stromal cells (Cassese et al, 2003; Wardemann et al, 2004; Cretu & Brooks, 2007; Wols et al, 2014). These reports have also indicated the importance of IL-6 for the maintenance of plasma cells in vitro as well as playing a key role in the pathogenesis in myeloma cells (Scheller et al, 2011; Schwendener & Mete, 2014). Thus, new models are necessary to investigate the molecular mechanisms that regulate PC homeostasis.…”
Section: Introductionmentioning
confidence: 98%
“…(15,16) Tumor associated macrophages (TAM) is a major component of the inflammatory cells those infiltrate in the tumor microenvironment, derived from the white blood cells from bone marrow and evolved from peripheral blood monocytes. (17) Studies have shown that there are two polarization types of TAM in different environmental conditions, i.e., M1 and M2. (18) Among them, M2 polarization inhibits the anti-tumor immune response and releases various factors, to directly or indirectly promote tumor angiogenesis, tumor growth and tumor metastasis.…”
mentioning
confidence: 99%